Activity based Learning of Chemical Reactions at the Secondary Level - Sharma, R. K. (SCHOOL SCIENCE, 2015)
In the present study activity based learning method was employed in learning chemical reactions at the secondary level in an SC/ST dominated rural school. For effective participation of students in learning chemical reactions, activities like group exercise, group work, quiz, seminar and projects were carried out. The students were also encouraged to participate in presentation of concepts of chemical reactions. Friendly environment was created for expression of thoughts and interaction of students during the teaching–learning process of chemical reactions.